LITERARY NORMS AND SPEECH CULTURE (Journal of Universal Science Research, 2023)
Speech culture studies the literary norm in order to define the boundaries and means of cultural speech with a specific purpose. Therefore, the field of speech culture evaluates and monitors literary language and its normative system.  The literary norm or linguistic norm or linguistic standard or language norm is a historically determined set of commonly used language assets, as well as rules for their selection and use, which have been recognized by society as the most appropriate in a particular historical period.